Persepsi Masyarakat tentang Pengembangan Standar Industri Hijau pada Usaha Batik untuk Mengurangi Dampak Pencemaran Limbah - Maghfiroh, Maghfiroh; Murty, Daru Anggara; Sasongko, Aditya Dimas Wahyu; Ariadi, Heri (JURNAL LITBANG KOTA PEKALONGAN, 2023)
The green batik concept of is very important to be developed in Pekalongan City. The aim of this research is to determine the level of public perception regarding efforts to develop batik green industry standards in Pekalongan City as an implementation step to reduce the impact of batik waste pollution. The method used is descriptive qualitative with data collection using purposive sampling. The results of the research show that the level of public perception regarding the meaning of green batik products and government policy regarding green products for batik is 68% and 65% of them understand. Responses to public perceptions of the green batik industry standard concept and its implementation showed a percentage of 63% and 62% who knew. The perception of public knowledge regarding green industry branding and its health risk impacts shows that 57% and 72% of batik producers know about it. 73% of the public's perception is that they know about procedures for managing batik materials and 65% also know about waste management. The conclusion from the research results shows that the level of public perception of efforts to develop green industry standards in Pekalongan City is very good. The level of public perception towards efforts to develop green industrial standards in the batik industry in Pekalongan City is good. Keywords: Industry, environment, batik maker, pollutant, respondents